2009
DOI: 10.1080/01443610902984953
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and pregnancy: Results of a survey at a Turkish women's hospital in 1,020 patients

Abstract: We aimed to investigate the level of knowledge about the effects of cigarette smoking and status before and during pregnancy. The study was performed on 1,020 pregnant women who attended the clinic for a routine visit. The questionnaire consisting of questions about sociodemographic data, smoking habits and knowledge about harmful effects of smoking on fetus (miscarriage, intrauterine growth retardation, pre-term birth, fetal mortality-morbidity, postpartum infant death, pre-term premature rupture of membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
1
13
1
3
Order By: Relevance
“…The rate of smoking in pregnancy in Turkey was reported to be 11.6% by Doğu and Berkiten (14), 12.8% by Altıparmak et al (26), and 14.8% by Karçaaltınçaba et al (27), which are consistent with that found in the current study, and the rate was reported as 54.8% by Durualp et al (8), which is higher than that in this study. According to TPHS, 15% of the pregnant women were .…”
Section: Discussionsupporting
confidence: 59%
“…The rate of smoking in pregnancy in Turkey was reported to be 11.6% by Doğu and Berkiten (14), 12.8% by Altıparmak et al (26), and 14.8% by Karçaaltınçaba et al (27), which are consistent with that found in the current study, and the rate was reported as 54.8% by Durualp et al (8), which is higher than that in this study. According to TPHS, 15% of the pregnant women were .…”
Section: Discussionsupporting
confidence: 59%
“…Active or passive smoke contains numerous compounds emitted in gases, many of which are oxidants and prooxidants, and is associated with numerous adverse pregnancy outcomes, including intrauterine growth retardation and fetal death [23,27]. The enhanced production of reactive oxygen species by smoke is related to increased free radical production, depleted serum antioxidants, and oxidative stress [3,6,18,28], which can result in the oxidation of lipids, induction of DNA single-strand breakage, inactivation of certain proteins, and the disruption of biological membranes [14,26,36].…”
Section: Introductionmentioning
confidence: 99%
“…Although we expect pregnant women not to smoke during pregnancy, data from both Turkey and other countries show that such an expectation is not realistic in today's world. For example, in previous Turkish study, Karcaaltincaba et al [23] declared that 14.0% of pregnant women were still smoking when they applied to the clinic for their control visit. Similarly, Uncu et al [24] reported a 9.8% frequency of smoking among 499 pregnant women who delivered at a university hospital in Bursa.…”
Section: Definitionsmentioning
confidence: 99%